2013
DOI: 10.1111/bcpt.12045
|View full text |Cite
|
Sign up to set email alerts
|

Cinnabar is Different from Mercuric Chloride in Mercury Absorption and Influence on the Brain Serotonin Level

Abstract: The toxicity of cinnabar, a naturally occurring mercury sulphide (HgS), has long been referred to soluble mercury chloride (HgCl 2 ). To investigate whether the speciation of mercury plays a role in its disposition and toxicity, we hereby investigated and compared cinnabar with soluble HgCl 2 and pure insoluble HgS in mice on mercury absorption, tissue distribution and in relation to the biological effects. The male C57BL/6J mice were treated by oral administration of various doses of cinnabar, with 0.01 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…and MeHg in mice after 44 days of administration [6]. Thus, it is not surprising that in the current study (30 mg/kg, po for 7 days), no overt toxicological effects and gene expressions related to liver toxicity and drug processing genes were found, in agreement with the literature that the bioaccebility of HgS is quite different from HgCl2 [36,37], resulting in much less toxicity potential [26,38]. Compared to prior studies on the induction of Cyp1a, 3a, and 4a genes [26,38], no apparent effects of cinnabar on cytochrome P450 is evident under the present experimental conditions (lower dose and shorter time).…”
Section: Expression Of Phase-2 Conjugation Enzyme Genessupporting
confidence: 93%
“…and MeHg in mice after 44 days of administration [6]. Thus, it is not surprising that in the current study (30 mg/kg, po for 7 days), no overt toxicological effects and gene expressions related to liver toxicity and drug processing genes were found, in agreement with the literature that the bioaccebility of HgS is quite different from HgCl2 [36,37], resulting in much less toxicity potential [26,38]. Compared to prior studies on the induction of Cyp1a, 3a, and 4a genes [26,38], no apparent effects of cinnabar on cytochrome P450 is evident under the present experimental conditions (lower dose and shorter time).…”
Section: Expression Of Phase-2 Conjugation Enzyme Genessupporting
confidence: 93%
“…We have previously shown that the kidney toxicity of HgS is much less than environmental mercurials in mice (300 mg/kg, po for 6 weeks) (Lu et al, 2011, and in rats (200 mg/kg, po for 60 days) (Shi et al, 2011). Thus, it is not surprising that in the current study (30 mg/kg, po for 7 days), no overt toxicological effects and gene expressions related to renal toxicity and transporters were found, in agreement with the literature about the bioaccebility of HgS (Koch et al, 2013;Wang et al, 2013;Tinggi et al, 2016) and our recent studies on cinnabar-containing traditional medicines on renal transporters (Zhu et al, 2014;Sui et al, 2015). However, it should be noted that the higher dose and longer-time of cinnabar administration, renal toxicity did occur (400-800 mg/kg, po for 90 days in rats) (Liang et al, 2009).…”
Section: Expression Of Renal Efflux Transporterssupporting
confidence: 91%
“…In mice treated with HgCl 2 (10 mg/kg) and 10-fold higher HgS (100 mg/kg) or cinnabar for 10 days, the Hg concentrations in the brain, serum, liver, and kidney of HgCl 2 -treated mice were 15-, 20, 65- and 87-fold higher than HgS groups, respectively. Most importantly, only HgS could significantly decrease brain serotonin levels, whereas HgCl 2 was ineffective [78].…”
Section: Chemical Compositions Of Metals Determine Therapeutic Effmentioning
confidence: 99%